Neutralizing Monoclonal Antibodies Block Human Immunodeficiency Virus Type 1 Infection of Dendritic Cells and Transmission to T Cells - Frankel, Sarah S. (American Society for Microbiology, 1998)
Prevention of the initial infection of mucosal dendritic cells (DC) and interruption of the subsequent transmission of HIV-1 from DC to T cells are likely to be important attributes of an effective human immunodeficiency virus type 1 (HIV-1) vaccine. While anti-HIV-1 neutralizing antibodies have been difficult to elicit by immunization, there are several human monoclonal antibodies (MAbs) that effectively neutralize virus infection of activated T cells. We investigated the ability of three well-characterized neutralizing MAbs (IgG1b12, 2F5, and 2G12) to block HIV-1 infection of human DC. DC were generated from CD14(+) blood cells or obtained from cadaveric human skin. The MAbs prevented viral entry into purified DC and the ensuing productive infection in DC/T-cell cultures. When DC were first pulsed with HIV-1, MAbs blocked the subsequent transmission to unstimulated CD3(+) T cells. Thus, neutralizing antibodies can block HIV-1 infection of DC and the cell-to-cell transmission of virus from infected DC to T cells. These data suggest that neutralizing antibodies could interrupt the initial events associated with mucosal transmission and regional spread of HIV-1.